ESG and Financial Risk in ASEAN-5: Mediating Role of Financial Constraints - Azmi, Nurul Farida; Hendranastiti, Nur Dhani (LP2M IAIN Palopo, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) scores, both in aggregate and by individual pillars (Environmental, Social, and Governance) on financial risk, and examines the mediating role of financial constraints measured using the SA Index. The analysis uses 595 firm-year observations from 119 non-financial publicly listed companies in ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Thailand, and Singapore) during the period 2019–2023. Financial risk is proxied by the Altman Z-Score, and the model is estimated using panel data regression with the Two-Stage Least Squares (2SLS) method, Driscoll-Kraay standard errors to address potential endogeneity and heteroskedasticity, and Random Effects model. The results show that only the Social (S) pillar has a significant and positive direct effect on the Altman Z-Score, indicating a reduction in financial risk, while aggregate ESG, Environmental (E), and Governance (G) scores show no significant direct impact. However, all ESG components are significantly negatively associated with financial constraints, implying that better ESG performance improves internal financial conditions. Mediation analysis using the coefficient-based approach and Sobel Test confirms that financial constraints significantly mediate the relationship between ESG and financial risk. These findings emphasize the importance of ESG integration in financial management as a strategy to mitigate bankruptcy risk in developing economies